Conceptual design of two-plate injection mould for UMP's keychain - Azhar, Yusop (2008)
UMPs keychain is a small product made from plastic same as UMP (University Malaysia Pahang) logo. Demand on plastic product in this country is very tremendous because plastic product has better in quality, design and appearance than any material product. To produce better quality of plastic product, it needs to have some processes and most important is initially in design stages. High quality plastic product can be produced using injection molding process that required good design of mold. In design the plastic mold the most important thing is get the suitable size runner and gate system. This project is using Moldflow Mold Adviser software in order to get achieve optimum size runner and gate system for two-plate injection mold for UMP's keychain.